The Role of Sole Proprietorships and Notaries in Developing Female MSME Entrepreneurs in Sumatera - Rohana Amelia Putri Handayani; Rouli Anita Velentina (Journal of Law and Policy Transformation, 2025)
Women-led micro, small, and medium enterprises (MSMEs) in Sumatra continue to face structural barriers, particularly limited access to formal legal status, capital, and regulatory certainty. This study aims to analyze the role of the Sole Limited Liability Company (Sole LLC) framework and Notaries in supporting the development of female MSME entrepreneurs in Sumatra, as well as to identify the key factors inhibiting their business growth. The research employs a normative juridical approach supported by literature review and secondary data analysis on regulatory frameworks and MSME conditions in Indonesia. The findings indicate that the Sole LLC mechanism simplifies business legalization for individual entrepreneurs, reduces administrative burdens, and enhances access to financial institutions. Notaries play a strategic role in ensuring legal certainty, facilitating business establishment, and providing legal guidance that strengthens institutional legitimacy. However, legal facilitation alone is insufficient without parallel improvements in financial literacy, digital capacity, and policy outreach. This study contributes to the discourse on women’s economic empowerment by demonstrating that legal institutional reform—particularly through simplified corporate structures and professional legal support—can function as a structural enabler of inclusive economic development, while highlighting the need for integrated policy support beyond formal legalization.